Analgesic Activity of Ethanol Extract of Temu Giring Rhizome (Curcuma heyneana Val & Zijp) in Mice - Marianne; Khairunnisa; Wilda (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Temu giring (Curcuma heyneana Val & Zijp) is a traditional medicinal plant that is believed in community as an analgesic. The objective of this research was to determine the analgesic activity of the C. heyneana rhizome by using infra red (IR) thermal induction method in mice. Mice were divided into 7 groups. Group 1 served as negative control, group 2,3,4,5 served as treatment groups which is given ethanolic extract of C. heyneana rhizome at dose of 5, 25, 125, and 625 mg/kg respectively, group 6 and 7 served as comparable groups, given antalgin 65 mg/kg and morphine sulphate 1.3 mg/kg respectively. The observation have been done, included to pain resistance of mice which exposed by infra red (IR) every 10 minutes for 80 minutes. The data were analyzed by ANOVA at the significance level of 95%. Ethanolic extract of C. heyneana at the doses of 25, 125, and 625 mg/kg had significant effect to reduce the pain compared to the negative control (p<0.05). Ethanolic extract of C. heyneana rhizome at dose of 125 mg/kg, had the same effect to antalgin 65 mg/kg (pâ‰¥0.05), while the ethanolic extract of C. heyneana at the dose of 625 mg/kg had the same effect as morphine sulfate 1.3 mg/kg (pâ‰¥0.05). It can be concluded that ethanolic extract of C. heyneana rhizome has analgesic activity. Keywords: temu giring, analgesic, Curcuma heyneana, rhizome